Rancangan Pembuatan Website Jurusan Desain Komunikasi Visual (Dkv) Universitas Bina Nusantara - Widhyatmoko, Danu (Humaniora, 2010)
The purpose of this article is to describe a design process of a website utilized by the Department of DKV, Bina Nusantara University. The website description was done by using literature methods such as analysis of similar websites, and using the website design method developed by Gene DeFazzio. From the analysis results can be obtained data classification needs and system as expected by DKV BINUS website. Then, from the data analysis, website was developed through the stages of Pre-Production, Production, and Uploading. Through this process, it has been produced a website which serves as a database and information, and supports the process of marketing and branding of the Department of DKV BINUS.